Cows of reproductive age in the high Andean region of Peru have seroprevalence of antibodies against bovine herpesvirus 1 and Neospora caninum - Contreras Vílchez, Víctor (2025)
Objective To determine the seroprevalence of infectious agents with reproductive implications in cattle from 3 districts of the high Andean region of Peru over 3,500 m above level sea. Methods 361 blood samples were collected from cows in 3 districts of the Apurimac department using nonprobabilistic stratified sampling for an exploratory study. Antibodies against Brucella spp, Mycobacterium avium subsp paratuberculosis, bovine viral diarrhea virus, bovine leukemia virus, bluetongue virus, bovine herpesvirus 1 (BHV), and Neospora caninum (NC) were detected by ELISA. Analysis of independence, multiple correspondence, and logistic regression were performed for risk factors, with district, age, and phenotypic traits as predictors. Results The highest seroprevalences were 18.28% BHV and 6.93% NC, with a similar trend at the sector and herd levels. Bovine herpesvirus 1 was predominant in Cotaruse and Oropesa and NC in Oropesa and San Jerónimo. The multiple correspondence analysis explained 42.40% of the structural variability, with greater dispersion observed between seropositives for NC and BHV, without a significant association between seropositivities. The district was a risk factor for NC, with a 95% CI of 0.11 to 0.88 in Cotaruse, although the 95% CI for BHV was 7.33 to 630.75 in Cotaruse and 14.11 to 1,289.94 in Oropesa. Conclusions BHV and NC are seroprevalent in cows from the sampled high Andean herds, and district location is the strongest risk factor. Clinical Relevance Environmental conditions and livestock management practices of the region could explain the seroprevalence rates; however, strengthening surveillance against BHV and NC is imperative to prevent risks of acute or subclinical infections.